Peer-to-peer shadowing as a technique for the development of nurse middle managers clinical leadership: An explorative study. Issue 4 (2nd October 2017) - Lalleman, Pieterbas; Bouma, Joanne; Smid, Gerhard; Rasiah, Jananee; Schuurmans, Marieke
Abstract : Purpose: The purpose of this study was to explore the experiences and impact of peer-to-peer shadowing as a technique to develop nurse middle managers' clinical leadership practices. Design/methodology/approach: A qualitative descriptive study was conducted to gain insight into the experiences of nurse middle managers using semi-structured interviews. Data were analysed into codes using constant comparison and similar codes were grouped under sub-themes and then into four broader themes. Findings: Peer-to-peer shadowing facilitates collective reflection-in-action and enhances an "investigate stance" while acting. Nurse middle managers begin to curb the caring disposition that unreflectively urges them to act, to answer the call for help in the here and now, focus on ad hoc "doings", and make quick judgements. Seeing a shadowee act produces, via a process of social comparison, a behavioural repertoire of postponing reactions and refraining from judging. Balancing the act of stepping in and doing something or just observing as well as giving or withholding feedback are important practices that are difficult to develop. Originality/value: Peer-to-peer shadowing facilitates curbing the caring disposition, which is essential for clinical leadership development through unlocking a behavioural repertoire that is not easy to reveal because it is, unreflectively, closely knit to the professional background of the nurse managers. Unlike most leadership development programmes, that are quite introspective and detached from context, peer-to-peer shadowing does have the potential to promote collective learning while acting, which is an important process.